Edukasi Keluarga Berencana (KB) pada Pasangan Usia Subur (PUS) di Dusun Ii Desa Nunkurus Kupang Timur - Avelina Paskalia Gusman; Maria Magdalena Theofila Duka (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Family planning (KB) is one of the government's efforts to control population growth and create quality families. KB is one of the main targets of national development. A fertile couple is a married couple who currently live together, whether officially residing or not, where the wife's age is between 20 and 45 years. This community service activity aims to provide education to fertile couples about family planning. Contraceptive methods can be divided into two, namely long-term contraceptive methods (MKJP) such as IUDs, implants, MOW, MOP and short-term contraceptive methods (non-MKJP) such as condoms, injections and pills. The methods used in this activity are lectures, brainstorming, discussions and questions and answers. This activity was held on Tuesday, December 2, 2025, starting at 09.00 WITA and ending at 11.00 WITA. The target was all fertile couples in Dusun II Padang Beringin in Nunkurus Village. This outreach activity began with participants filling out a pre-test, then continued with lectures, discussions, questions and answers and ended with participants filling out a post-test questionnaire. The results of this community service show an increase in knowledge of fertile couples about family planning. The resource person for this activity was a lecturer from STIKes Maranatha Kupang. This community service activity that has been carried out is to increase the knowledge of fertile couples about family planning